Gold‐Silver Catalysts: Ruling Factors for Establishing Synergism. Issue 16 (12th June 2019) - Stucchi, Marta; Jouve, Andrea; Villa, Alberto; Nagy, Gergely; Németh, Miklòs; Evangelisti, Claudio; Zanella, Rodolfo; Prati, Laura
Abstract: DPU and SOL immobilisation have been used to prepare 1 %AuAg/TiO2 with internal ratio 1 : 1 and 4 : 1 which have been studied as fresh, calcined in air at 300 °C and reduced at 550 °C in H2 . TEM‐EDS, XPS, UV‐Vis and CO‐DRIFT allowed to characterize the samples in terms of particle size, particle composition, exposure and oxidation state of metals. Correlating these characteristics to the catalytic behaviour we concluded that only Au‐rich catalysts show synergistic effect, silver in bimetallic systems appears more resistant to oxidation than in monometallic one, thermal treatment enhances the SMSI thus producing (regardless to the post‐treatment) almost the same amount of Au δ+ and also Ag δ+ . Catalysts prepared by DPU (calcined in air or reduced in H2 ) are more active than SOL (fresh or calcined) probably due to the higher presence of gold at the surface. Abstract : Silver and Gold ! Au−Ag catalysts by DPU and SOL immobilisation have been studied as fresh, calcined in air or reduced in H2, for glycerol oxidation. TEM‐EDS, XPS, UV‐Vis and CO‐DRIFT provided particle size and composition, exposure and oxidation state of metals. Morphological features were correlated to the catalytic behaviour, concluding that Au‐rich catalysts show a positive synergistic effect enhancing the catalytic behaviour toward the glycerol oxidation. DPU and SOL techniques creates different structure.